2020
DOI: 10.1002/pep2.24197
|View full text |Cite
|
Sign up to set email alerts
|

Synergy among humimycins against methicillin‐resistant Staphylococcus aureus

Abstract: Drug resistant and multidrug resistant microorganisms are an increasing problem for public health. In this work, we investigate the ability of lipopeptides to act synergistically as a potential treatment for methicillin resistant Staphylococcus aureus (MRSA) infections. We present results on a specific class of lipopeptides: humimycins. We explored various changes to their structure including altering their hydrophobicity and enantiomeric amino acid substitutions. Of specific note, the "dehydroxy" analogue, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In our own previous work we found that myristic acid-modified peptides are able to work synergistically with other antimicrobial drugs ( 11 ). We hypothesized that a lipid tail would be essential for interaction with a lipid-flipping enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…In our own previous work we found that myristic acid-modified peptides are able to work synergistically with other antimicrobial drugs ( 11 ). We hypothesized that a lipid tail would be essential for interaction with a lipid-flipping enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] MRSA is highly resistant to cefoxitin, ciprofloxacin, gentamicin, and other antibiotics. 4,5 The most commonly used treatments for MRSA infection include radiation, 6 antibiotic, 7,8 surfactant molecular, 9 and nanomaterial 10 therapies; among these, antibiotic therapy is the first choice in many cases. However, antibiotic resistance remains one of the leading causes of death worldwide.…”
Section: Introductionmentioning
confidence: 99%